EXAMINING THE LINKAGES BETWEEN TECHNOLOGY ADOPTION AND COMPONENTS OF CORN AGRIBUSINESS - Aulia Radjaloa, Vhyda Hamidah (PROCURATIO: Jurnal Manajemen & Bisnis, 2024)
This research delves into the complex relationship between technology adoption and the various components of corn agribusiness, with a focus on Indonesia's South Oba District. Corn, a key national commodity, faces challenges in meeting production targets set by the Ministry of Agriculture. This study investigates how technology adoption influences corn agribusiness aspects, including productivity, economic integration, and social and environmental impacts. Utilizing a quantitative approach, the research involves purposive sampling of 70 corn farmers and assesses agribusiness and cultivation technology through indicators like seed usage, soil processing, and agro-input systems. Findings reveal that despite high technology adoption, certain subsystems, notably agro-marketing and agro-industry, require improvement. The study underscores the interdependence between technology adoption and subsystems, emphasizing the need for targeted development in agro-marketing, agro-supporting services, agro-industry, agro-input, and agro-production. Recommendations include enhancing marketing strategies, improving support services, developing the agroindustry value chain, ensuring quality agro-inputs, and implementing sustainable farming practices. This interdisciplinary research aims to provide insights for policymakers, agribusiness practitioners, and researchers to navigate challenges and harness opportunities in the modernization of corn agribusiness.